2019
DOI: 10.1101/583468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic association study of psychotic experiences in UK Biobank

Abstract: Psychotic experiences, such as hallucinations and delusions, are reported by approximately 5%-10% of the general population, though only a small proportion of individuals develop psychotic disorders such as schizophrenia or bipolar disorder. Studying the genetic aetiology of psychotic experiences in the general population, and its relationship with the genetic aetiology of other disorders, may increase our understanding of their pathological significance. Using the population-based UK Biobank sample, we perfor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
2
4
1
Order By: Relevance
“…Contrary to recent genetic evidence based on psychotic experiences in adulthood (21), psychosis spectrum symptoms in youth did not yield a general association with multiple psychiatric illnesses, but with ADHD specifically. While an association between schizophrenia genetic risk and psychosis symptoms has been reported in adults, the lack of such an association in our study is consistent with previous literature in adolescents (in a population sample of >5k genotyped youth aged 12-18, no such association was observed (22)).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to recent genetic evidence based on psychotic experiences in adulthood (21), psychosis spectrum symptoms in youth did not yield a general association with multiple psychiatric illnesses, but with ADHD specifically. While an association between schizophrenia genetic risk and psychosis symptoms has been reported in adults, the lack of such an association in our study is consistent with previous literature in adolescents (in a population sample of >5k genotyped youth aged 12-18, no such association was observed (22)).…”
Section: Discussioncontrasting
confidence: 99%
“…The heritability of psychotic experiences has been estimated between 30-50% from twin studies (18,19) with the proportion of genetic variance explained by common variants (SNP-heritability) of 3-17% in adolescents (18,20). Adults with psychotic symptoms harbor increased genetic liability for a broad spectrum of psychiatric disorders, including schizophrenia and other neuropsychiatric disorders (21). While in adolescents some evidence suggests increased genetic risk for schizophrenia (and major depressive disorder) for specific features of psychosis (18), the reported effect sizes are very small, and these effects not very robust (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that non-additive genetic influences or rare variants are shared across psychotic experiences measures and age. In an independent report, genetic risk for psychotic experiences in adults did not predict psychotic experiences in 12 year olds or 16 year olds, in agreement with our findings of lack of genetic overlap across adolescent and adult psychotic experiences, although there was some evidence of genetic association with psychotic experiences at age 18 years (55). Because UK Biobank participants were asked to report on psychotic experiences across their lives, some may have referred to experiences such as hallucinations in later adulthood that can occur as part of conditions such as dementia, eye conditions, Charles Bonnet syndrome and medication side effects, which may have different etiologies to psychotic experiences in adolescence.…”
Section: Discussionsupporting
confidence: 91%
“…We found that positive psychotic experiences in the UK Biobank shared a moderate to substantial amount of common genetic variation with depression and schizophrenia, specifically experiences of auditory and visual hallucinations (un-real voices and un-real vision) and paranoid beliefs (believing in conspiracies) with schizophrenia (r g = 0.27 - 0.67) and with depression (r g = 0.41 - 0.96), consistent with an independent report (55). Our MR analyses indicated that liability to schizophrenia may be directionally associated with a propensity to believe in un-real conspiracies, and that liability to depression may be directionally associated with a propensity to report un-real voices and conspiracies.…”
Section: Discussionsupporting
confidence: 89%